A review of corneal melting following kerato‐refractive surgery. (9th July 2012) - Hodge, Christopher; Chan, Colin; Bali, Shveta Jindal; Sutton, Gerard
<x xml:space="preserve">Abstract</x> Corneal melting is a rare complication that may occur following a number of different types of surgery. Keratolysis may lead to scarring, irregular astigmatism, photophobia and decreased vision. This article reviews the incidence, pathophysiology and treatment of this condition in kerato‐refractive surgery.